Social contributors to cardiometabolic diseases in indigenous populations: an international Delphi study - Stoner, L.; Matheson, A.; Perry, L.; Williams, M.; McManus, Alexandra; Holdaway, M.; Dimer, L.; Joe, J.; Maiorana, Andrew (Elsevier Ltd., 2018)
© 2018 The Royal Society for Public Health Objective: The objective of this study was to identify priority social factors contributing to indigenous cardiometabolic diseases. Study design: A three-round Delphi process was used to consolidate and compare the opinions of 60 experts in indigenous cardiometabolic health from Australia, New Zealand and the United States. Methods: Round one: three open-ended questions: (i) historical, (ii) economic and (iii) sociocultural factor contributors to cardiometabolic disease risk. Round two: a structured questionnaire based on the results from the first round; items were ranked according to perceived importance. Final round: the items were reranked after receiving the summary feedback. Results: Several key findings were identified: (i) an important historical factor is marginalisation and disempowerment; (ii) in terms of economic and sociocultural factors, the panellists came to the consensus that the socio-economic status and educational inequalities are important; and (iii) while consensus was not reached, economic and educational factors were also perceived to be historically influential. Conclusion: These findings support the need for multilevel health promotion policy. For example, tackling financial barriers that limit the access to health-promoting resources, combined with improving literacy skills to permit understanding of health education.